Robust cooperative beamforming for SC-FDMA based multi-relay networks - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (2014 IEEE International Conference on Communications (ICC), 2014)
In this work, we propose a robust cooperative relay beamforming (rBF) design for single-carrier frequency-division multiple access (SC-FDMA) based multiuser multi-relay systems with imperfect channel state information. We maximize a lower bound on the achievable bit rate (ABR) of the network, subject to an aggregate relay transmit power constraint. Employing the primal decomposition technique, we decompose the problem into two subproblems: the rBF coefficient optimization and the relay power allocation. For a given power allocation across the frequency tones, a closed-form solution for the rBF matrices is obtained first. Subsequently, the convexity of the remaining power allocation problem is then proved, and efficient convex optimization methods are employed to find the global optimum. Simulation results validate the excellent performance of the proposed rBF schemes and show their superiority compared to conventional non-robust designs.<br
Keywords: Relays; Channel estimation; Optimization; Vectors; Resource management; Noise; Matrix decomposition